2012
DOI: 10.1007/s10068-012-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and anti-inflammatory effect of quercetin and its glycosides isolated from mampat (Cratoxylum formosum)

Abstract: In this study, quercetin, quercetin-3-O-β-Dglucopyranoside (isoquercitrin), quercetin-3-O-β-D-galactopyranoside (hyperin), and quercertin-3-O-α-L-rhamnoside (quercitrin) from mampat (Cratoxylum formosum) were isolated and their antioxidative and anti-inflammatory activities were investigated. Quercetin displayed weaker antioxidant activity than its glycosides, while the cellular antioxidant capacity of quercetin and hyperin was stronger than that of isoquercitrin and quercitrin, indicating that the higher cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 31 publications
1
50
0
1
Order By: Relevance
“…indicating that the higher cell-membrane permeability of quercetin and hyperin than isoquercitrin and quercitrin was due to the different hydrophobicity and the specific membrane receptor for galactose (Choi et al, 2012). Lin and others (2011) …”
Section: Renmentioning
confidence: 95%
“…indicating that the higher cell-membrane permeability of quercetin and hyperin than isoquercitrin and quercitrin was due to the different hydrophobicity and the specific membrane receptor for galactose (Choi et al, 2012). Lin and others (2011) …”
Section: Renmentioning
confidence: 95%
“…Quercetin‐3‐glucoside and quercetin have also been reported as the major flavonoids in the grape marc and mango puree (Bonilla, Mayen, Merida, & Medina, ; Schieber, Ullrich, & Carle, ). It has been demonstrated that quercetin and its glucosides have antioxidant, antiproliferative, and anti‐inflammatory properties (Choi, Tai, Cuong, Kim, & Jang, ; de Araujo et al, ; Kobori et al, ). Moreover, several studies have reported that there is a significant inverse correlation between the quercetin consumption and the prevalence of chronic hepatic injuries (Kobori, Masumoto, Akimoto, & Oike, ; Snyder et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical studies on C. formosum subsp. pruniflorum reported antioxidant activity of the ethanolic leaf extract (Yingngam et al, 2014), anti-inflammatory activity of phenolic compounds, xanthones, quinone, quercetin and its glycosides from leaves (Choi et al, 2012;Xiong et al, 2014), anticancer activity of ethanolic twig extract, hot water leaf extract and ethanolic leaf extract (Machana et al, 2012;Issara-Amphorn and T-Thienprasert, 2014) antibacterial and cytotoxic activities of xanthones, anthraquinones and qiunonoids from the roots and bark (Boonnak et al, 2006;Boonsri et al, 2006;Boonnak et al, 2007), antifungal and cytotoxic activity of gum extract (Thaweboon et al, 2014), anti-gastric ulceration of ethanolic leaf extract in rats (Sripanidkulchai et al, 2010) and anti-proliferation and antimigration activity of human breast cancer MCF-7 cells from leaf extract (Buranrat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%